Systematic literature review: Kemampuan literasi matematis ditinjau dari kemandirian belajar siswa - Iir Amelia; Novaliyosi Novaliyosi; Cecep Anwar Hadi Firdos Santosa; Abdul Fatah (Universitas Sultan Ageng Tirtayasa, 2023)
Independent learning is one of the most important things to improve mathematical literacy skills. This study aims to conduct a literature review related to mathematical literacy skills in terms of student learning independence. The research method used in this research is SLR (Systematic Literature Review). Data collection is done by identifying or reviewing all articles that have the same research topic in this study. The articles used in this study were 28 national and international journal articles. The articles used were then analyzed and tabulated in a table in the form of the author's name, journal and research results. From this study, it was found that students with high learning independence tend to be able to solve mathematical literacy problems well, fulfill the three components of the completion process and the 7 components of the basic competence of mathematical literacy tend to be achieved. Students with moderate learning independence still make mistakes in the process of completion and final results, then they have not fulfilled all the components of the basic competence of mathematical literacy. Students with low learning independence make mistakes in solving mathematical literacy problems, cannot perform process skills well and cannot write the final answer correctly.